Islamic architecture in Iran poststructural theory and the architectural history of Iranian Mosques - Khaghani, Saeid (International library of Iranian studies, 2012)
"The architecture of the Islamic world is predominantly considered in terms of a dual division between "tradition" and "modernity" - a division which, Saeid Khaghani here argues, has shaped and limited the narrative applied to this architecture. Khaghani introduces and reconsiders the mosques of eighth- to fifteenth-century Iran in terms of poststructural theory and developments in historiography in order to develop a brand new dialectical framework. Using the examples of mosques such as the Friday Mosques in Isfahan and Yazd as well as the Imam mosque in Isfahan, Khaghani presents a new way of thinking about and discussing Islamic architecture, making this valuable reading for all interested in the study of the art, architecture, and material culture of the Islamic world."